The Middle Cretaceous Shallow to Deep Carbonates of the Sarvak Formation, Zagros Basin, Southwest Iran: Paleoenvironmental Reconstruction and Sequence Stratigraphy - kiarostami, kiana; Aleali, Mohsen; Aghanabati, Ali (Anuário do Instituto de Geociências, 2025)
The main purpose of this study is to investigate the sedimentary environment conditions and sedimentary characteristics of Sarvak Formation and therefore, due to the importance of Sarvak Formation in the Zagros Basin, in the present study, facies features, sedimentary environment and sequence stratigraphy of the mentioned formation were identified. In the present study, one stratigraphic section located in Bangestan Anticline (Tang-e-Sarvak) was studied to determine and analyze the facies types, depositional environment, and sequence stratigraphy characteristics of the Sarvak Formation in northwest of Behbahan city. This section is mainly composed of medium to thick-bedded and massive limestone. Facies analysis led to the recognition of 11 microfacies related to the pelagic, outerramp, middle-ramp, and inner-ramp environments. Facies frequency analysis of the microfacies and facies belt demonstrated that the most frequency was related to the MF2 belonging to the pelagic environment and the lowest frequency was related to the MF8 belonging to the inner ramp environment. Studying the changes of vertical facies and their comparison with their modern and ancient counterparts indicated that the Sarvak Formation has been deposited in a shallow carbonate ramp platform. The sequence stratigraphic assessments indicated that the Sarvak Formation consists of three third-order depositional sequences, each consisting of transgressive and highstand system tracts. Typical intervals, such as sequence boundaries, maximum flooding surfaces, stacking patterns, and system tracts were also distinguished.